Open source intelligence, social media and law enforcement: Visions, constraints and critiques. (August 2015) - Trottier, Daniel
This article considers how recent developments in open source intelligence impact the inclusion of social media data in policing, and how these changes are a reflection of technological affordances by platform developers and private third-party companies, as well as police cultural and institutional constraints. It explores the institutional contexts in which social media open source intelligence is trialled in Europe by drawing on interviews with police officials and privacy advocates from 13 European Union member states. Respondents considered their adoption of open source social media monitoring technologies in their jurisdiction, locating this uptake within a context of technological scepticism. While open source intelligence infused with social media data enables an immediate access to social life for investigators, so too do they provoke a preoccupation with the origins and circulations of this content. This tension dovetails with institutional concerns, including a lack of specialised staff, budget constraints, along with a lack of clear legal and procedural protocols.